2017
DOI: 10.1093/mmy/myx043
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of Sporothrix schenckii complex biofilms

Abstract: Sporotrichosis, caused by species of Sporothrix schenckii complex, is the most prevalent subcutaneous mycosis in many areas of Latin America. The aim of this study was to evaluate the ability of Sporothrix spp. to form biofilms in vitro and to characterize the growth kinetics, morphology, and antifungal susceptibility of biofilms against classical antifungals. We investigated the ability of strains to produce biofilms in vitro and determined the effects of exposure to amphotericin B, itraconazole, caspofungin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…After 144 h, both strains produced consistent and mature biofilms, reaching the stationary phase between 144 and 168 h. Compared to other fungal pathogens, as Candida spp. (Sańchez-Vargas et al, 2013;Chandra and Mukherjee, 2015) and Cryptococcus neoformans (Martinez and Casadevall, 2007), our results showed that H. capsulatum exhibits a slower growth as a biofilm structure, similar to those found on Paracoccidioides brasiliensis (Sardi et al, 2015) and Sporothrix schenckii complex (Brilhante et al, 2018) biofilms. Also, EH-315 formed a more robust biofilm compared to G186A, corroborating with the findings of Goncalves et al (2020).…”
Section: Discussionsupporting
confidence: 79%
“…After 144 h, both strains produced consistent and mature biofilms, reaching the stationary phase between 144 and 168 h. Compared to other fungal pathogens, as Candida spp. (Sańchez-Vargas et al, 2013;Chandra and Mukherjee, 2015) and Cryptococcus neoformans (Martinez and Casadevall, 2007), our results showed that H. capsulatum exhibits a slower growth as a biofilm structure, similar to those found on Paracoccidioides brasiliensis (Sardi et al, 2015) and Sporothrix schenckii complex (Brilhante et al, 2018) biofilms. Also, EH-315 formed a more robust biofilm compared to G186A, corroborating with the findings of Goncalves et al (2020).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it has been suggested that, at least in experimental models, S. brasiliensis is more virulent in vivo than the other species [ 9 ]. In vitro, it has also been shown that Sporothrix brasiliensis has a greater ability to disarm murine macrophages, promoting its survival within macrophages (L. Rossato, PhD, S. A. Almeida, PhD, 2017, unpublished data), and to form biofilms [ 10 ]. In fact, biofilm-like structures were observed in patient 2’s CSF ( Figure 1C ), which may help to explain the recurrent hydrocephalus shunt catheter obstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation of Sporothrix species filamentous forms was performed according to Brilhante et al [3]. An aliquot of 200 µl containing 1×10 6 conidia ml -1 was prepared in RPMI 1640 medium and added to 96-well microplates.…”
Section: Effect Of Statins On Sporothrix Species Biofilmsmentioning
confidence: 99%
“…In order to establish themselves in the host organism, fungi have several virulence factors, including the ability to form biofilms, which are composed of cells that form microcolonies attached to a substrate recognized by the extracellular matrix, which allows or detects whether the microorganism is in a hostile or protected environment regarding host immune defence [3][4][5]. Among the virulence factors that contribute to the survival of S. schenckii complex species, biofilm formation has been described for both filamentous and yeast forms [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%